Emerging markets and the international financial architecture: A blueprint for reform - Jan Kregel (Levy Economics Institute of Bard College, 2015)
If emerging markets are to achieve their objective of joining the ranks of industrialized, developed countries, they must use their economic and political influence to support radical change in the international financial system. This working paper recommends John Maynard Keynes's "clearing union" as a blueprint for reform of the international financial architecture that could address emerging market grievances more effectively than current approaches. Keynes's proposal for the postwar international system sought to remedy some of the same problems currently facing emerging market economies. It was based on the idea that financial stability was predicated on a balance between imports and exports over time, with any divergence from balance providing automatic financing of the debit countries by the creditor countries via a global clearinghouse or settlement system for trade and payments on current account. This eliminated national currency payments for imports and exports; countries received credits or debits in a notional unit of account fixed to national currency. Since the unit of account could not be traded, bought, or sold, it would not be an international reserve currency. The credits with the clearinghouse could only be used to offset debits by buying imports, and if not used for this purpose they would eventually be extinguished; hence the burden of adjustment would be shared equally - credit generated by surpluses would have to be used to buy imports from the countries with debit balances. Emerging market economies could improve upon current schemes for regionally governed financial institutions by using this proposal as a template for the creation of regional clearing unions using a notional unit of account.
Keywords: E42; E52; F12; N44; 330; Banking Principle; Bretton Woods; Creditor Countries; Debtor Countries; Emerging Market Economies; Gold Standard; International Monetary Standard; Keynes; Reparations; Schacht; Triffin